Effect of surgical techniques in the treatment of small saphenous vein insufficiency on clinical outcomes - Aysen Yaprak Engin; Fatih Islamoglu (Turkish Journal of Vascular Surgery, 2022)
Aim: This study aims to explore the effects of three techniques on postoperative symptom recurrence and clinical outcome and define the predictors. Material and Methods: A total of 121 patients (63 males, 58 females; mean age: 47.4±11.3 years; range, 32 to 73 years) who underwent stripping (n=45), ligation alone (n=36), or ligation and foam sclerotherapy (2% polidocanol, n=40) for varicosities due to small saphenous vein (SSV) insufficiency between January 2004 and December 2011 were included in the retrospective study. Preoperative and postoperative CEAP (Clinical, Etiological, Anatomical, and Pathophysiological), symptom recurrence, and Doppler findings were evaluated with univariate and multivariate analyses. Results: The mean follow-up was 25.8±20.4 months. The operation type did not have any effect on postoperative symptom recurrence, high CEAP (≥3), or clinical outcomes. Predictor of postoperative symptom recurrence was preoperative high CEAP (p=0.001, relative risk [RR]: 4.8); predictor of high postoperative CEAP was postoperative perforating vein insufficiency (p=0.001, RR: 5.148). In the ligation group, a preoperative SSV diameter >5 mm was predictive for both postoperative symptom recurrence (p=0.039, RR: 7.8) and high postoperative CEAP (p=0.002, RR: 1.901), and preoperative deep vein insufficiency was also predictive for postoperative symptom recurrence (p=0.044, RR: 1.304). In the stripping group, postoperative neuropathy was significant (p=0.041, RR: 4.168). There was no difference in Kaplan-Meier symptom-free survival curves (p=0.651), venous clinical severity scores, or Aberdeen Varicose Vein Questionnaire scores among groups. Conclusion: High ligation is not a good option for patients with large SSV diameters or deep vein insufficiency. High ligation with stripping comes with an increased risk of sural neuropathy. High ligation with foam sclerotherapy should be considered an effective method with the ability of the foam to spread over the branches and microvenous structures. Performing operations before progression to high CEAP classes or greater SSV diameters is considerable. [Turk J Vasc Surg 2022; 31(3.000): 140-7]